Association of gut microbiota with lactose intolerance and coeliac disease: a two-sample Mendelian randomization study - Han, Zongze; Ran, Ying; Li, Jiwen; Zhang, Xue; Yang, Hui; Liu, Jiangpeng; Dong, Shijing; Jia, Hao; Yang, Zhen; Li, Yanni; Guo, Liping; Zhou, Simin; et al. (Frontiers in Nutrition, 2024)
Background and objectives: Lactose intolerance and coeliac disease are common clinical nutrient malabsorption disorders, with an unclear pathogenesis and limited therapeutic options. It is widely believed that the gut microbiota plays an important role in many digestive disorders, but its role in lactose intolerance and coeliac disease is not yet clear. This study aimed to investigate the correlation between gut microbiota and lactose intolerance and coeliac disease. Materials and methods: This study utilized the genome-wide association study database to investigate the association between gut microbiota and lactose intolerance and coeliac disease using Mendelian randomization (MR). The robustness of our findings was confirmed through subsequent analyses including Cochrane's Q statistic, MR-Egger Intercept Regression, MR-PRESSO Global Test and Leave-one-out methods. Results: By employing the inverse variance weighted method, we identified that family Veillonellaceae, genus Oxalobacter and Senegalimassilia were protective against lactose intolerance, whereas genus Anaerotruncus, Eubacterium rectale group and Ruminococcus2 were found to be risk factors for lactose intolerance. Regarding coeliac disease, class Bacilli and Gammaproteobacteria, family FamilyXIII and Veillonellaceae, genus Eisenbergiella, Lachnoclostridium, RuminococcaceaeUCG014 and Ruminococcus2 were identified as protective factors, while class Betaproteobacteria, genus Eubacterium xylanophilum group and Blautia were risk factors. Furthermore, reverse the MR analysis did not reveal any evidence of a causal relationship between lactose intolerance or coeliac disease and the bacteria identified in our study. Conclusion: This study provides novel insights into exploring the role of gut microbiota in lactose intolerance and coeliac disease; however, further experiments investigations are required to elucidate the specific underlying mechanisms.